Can The Subaltern Speak in Contemporary Cuban Short Story? - Ebenhoch, Markus (2019)
After the fall of the Berlin Wall, the so-called “Special Period in Times of Peace” began in Cuba. As a consequence of the profound political and social changes, new post-revolutionary discourses emerged in Cuban narrative in the 1990s. This paper examines the representation of subaltern speech, especially the case of characters affected by economic misery, in a corpus of 120 short stories written between 1990-2000. Based on the theoretical concepts of Antonio Gramsci and Gayatri Spivak as well as on the themes dealt in the corpus, the results of the narratological analysis of those fifty-nine short stories that contain descriptions of poverty will be presented and discussed; furthermore, the status of the Cuban author, the literary characters and the literary language will be discussed. The analysis of the narrators is of great importance for the question of subaltern articulation: Among these fifty-nine stories are twenty-nine texts that use homodiegetic narrators, eighteen of which live in miserable conditions. Twenty-three short stories are characterized by heterodiegetic narrators, but in just two texts the readers are faced with an internal focalization that is framed within a subaltern perspective. Three of the seven stories that oscillate between homodiegetic and heterodiegetic narrators are built with poor storytellers.